STROKE OUTCOME PREDICTION USING ADMISSION NIHSS IN ANTERIOR AND POSTERIOR CIRCULATION STROKE - Kazi, Sahrish; Siddiqui, Maimoona; Majid, Sadaf (Journal of Ayub Medical College Abbottabad, 2021)
Background: Stroke is a worldwide disease with high morbidity. Various scales are used to measure the severity and outcome of stroke. National Institute of Health Stroke Scale (NIHSS) is a quantifiable scale used to assess stroke severity. However, it is biased towards anterior circulation stroke as compared to posterior circulation stroke, giving higher values in the former. Therefore, it is imperative to know the mean values of NIHSS in each group to predict the functional outcome. The main aim of the study is to compare the mean NIHSS at the time of admission for determining favourable and unfavourable functional outcome in anterior and posterior circulation ischemic stroke. Methods: It is a descriptive case study of six months' duration done in a Tertiary Care Hospital. All patients of 18 years and above with ischemic stroke involving single arterial territory presented in hospital within 72 hours were included. With the help of the WHO sample size calculator, a target population of 100 patients was determined with a confidence level of 95%. For mean difference we applied independent t test and t score with mean differences for NIHSS at admission and location of stroke has been calculated. Patients with haemorrhagic stroke, venous stroke secondary to Dural Sinus thrombosis, with concomitant disability because of any reason including previous stroke, stroke involving watershed areas and concomitant Acute Coronary Syndrome were excluded. A favourable outcome was defined as Modified Ranking scale score of ‰¤3 at 1-month post stroke. Results: In anterior circulation, mean baseline NIHSS was 11.3 [SD 7.4], while in posterior circulation, mean NIHSS was 7.30 [SD 7.6]. Comparing the means for functional outcome in anterior circulation using independent t test score, a lower baseline NIHSS score was independently predictive of a favourable outcome for patients with AC (OR 1.268, 95% CI 1.76 -1.358) and PC (OR 1.534, 95% CI 1.321-1.891) stroke. Conclusion: The mean NIHSS of good functional outcome group is much lower for posterior circulation stroke as compared to anterior circulation stroke which highlights the need for basing the decision of acute stroke emergency management on full neurological examination, rather than a single scale, especially if the posterior circulation stroke is in question